Hukuman bagi pelaku zina: perspektif ayat ahkam dan hadits ahkam - Azizah, Firly Kamilatul (Maliki Interdisciplinary Journal, 2024)
A B S T R A C T The concept of adultery is not uncommon in today's society. As if adultery is not one of the major sins, because doing it is a common thing. Although in the Qur'an it is very clear that adultery is a sin, even approaching it is a sin, let alone committing it. Therefore, the author will provide a brief explanation of the punishment for adultery from the perspective of the ahkam verse and the hadith of the ahkam. Then what is the position of a child born from an adultery that occurs. In this review, the technique used is a subjective exploration strategy that looks at case-based social peculiarities. In addition, the author conducts literature research. From this research it was found that adultery is defined as an intimate relationship between a woman and an unmarried man and actions that can lead to it. Adultery is punishable by a hundred lashes and stoning, depending on the type of adultery. If adultery is muhsan, then the punishment is the same. Meanwhile, Ghairu Muhsan was exiled for one year and given a hundred lashes for adultery. In addition, adulterers can be punished if their actions can be proven by the presence of four witnesses, the adulterer's confession, and qarinah.